Analisis Penilaian Kinerja Organisasi Perangkat Daerah di Kota Bandung - - - Meyliana; Lidya - Agustina; Chandra - Setiawan (Jurnal Akuntansi, 2018)
Satuan Perangkat Kerja Daerah (SKPD) is a compulsory subject to the Laporan Akuntabilitas Kinerja Instansi Pemerintahan (LAKIP) in Indonesia. Of the many SPKDs incorporated in the city or district governments throughout Indonesia, it was reported that none of them had achieved an A rating of the LAKIP they had compiled. This phenomenon forms the basis for our research to disclose other factors that might influence the assessment of LAKIP on performance appraisal systems for SKPD in Indonesia. Based on research conducted by Spekle and Verbeeten (2013) explained that there is a factor of contractibility that can affect the relationship between the performance appraisal system with the performance used as the dependent variable. Therefore, this study attempts to replicate previous research to test whether it will produce a similar conclusion or not. The type of this research is causal explanatory, where the sample comes from population 3 SKPD located in Bandung while Moderated Regression Analysis (MRA) is used as a data analysis techniquewhether interaction test is a special application of linear regression (multiplication of two or more independent variables).Keywords: Performance Assessment System, Performance, Contractibility, Satuan Perangkat Kerja Daerah (SKPD) Bandung, Public Sector’s Performance.